Epiphytic orchids and host trees diversity at Gunung Manyutan Forest Reserve, Wilis Mountain, Ponorogo, East Java - NINA DWI YULIA; SUGENG BUDIHARTA (Biodiversitas Journal of Biological Diversity, 2011)
Yulia ND, Budiharta S (2011). Epiphytic orchids and host trees diversity at Gunung Manyutan Forest Reserve, Wilis Mountain, Ponorogo, East Java. Biodiversitas 12: 22-27. Natural forests in Wilis Mountain have been destroyed by forest fires, landslides and illegal logging. As a consequence, biological diversity in this area is threatened by local extinctions, particularly of orchid species. This study was aimed to explore, document and analyze the diversity of epiphytic orchids at Gunung Manyutan Forest Reserve, a natural forest area in Wilis Mountain. Purposive sampling on 1 hectare (50 x 200 m2) eight subplots (25 x 50 m2) All data on orchid species were recorded including its number, host trees and zone of the host tree where the orchid attached. The results showed that there were 29 epiphytic orchid species recorded. Flickingeria angulata was the most abundant species (Relative Abundance of orchids/ %Fo = 38.74), continued by Appendicula sp. (%Fo = 10.91) and Eria hyacinthoides (%Fo=6.57). The three most important host trees were Pinus merkusii, Schima wallichii and Engelhardia spicata. Zone 3 (bottom part of the branches) was revealed as the most favorable part at the host tree (281 individuals), while Zone 1 (bottom part of the main stem) was the least preferable one.